Cost of management of severe pneumonia in young children: systematic analysis - Shanshan Zhang 1,2; Peter M. Sammon 1; Isobel King 1,3; Ana Lucia Andrade 4; Cristiana M. Toscano 4; Sheila N Araujo 4,5; Anushua Sinha 6; Shabir A. Madhi 7,8; Gulam Khandaker 9,10; Jiehui Kevin Yin 9,10; Robert Booy 9,10; Tanvir M Huda 11,12; et al. (Edinburgh University Global Health Society, 2016)
Childhood pneumonia is a major cause of childhood illness and the second leading cause of child death globally. Understanding the costs associated with the management of childhood pneumonia is essential for resource allocation and priority setting for child health.